BIODIVERSITY AND ABUNDANCE OF DEMERSAL FISHS STOCK IN TAMBELAN WATER, NATUNA SEA - . Fahmi; . Yonvitner (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
Understanding on fish diversity is essential for fish stock conservation specifically in Tambelan Island waters with a high fish diversity. This research was conducted in November 2010 at 6 sampling site around Tambelan Island. Samples were taken using trawl gear within sweeping technique. The para-meters of collected data were kind of species, number of fish, total length, and total weight. Data analyses were stock abundance (based on time trawling), diversity, richness, equity, and similarity between site sampling. The total fishes that were caugth were 1.224 individual that consisted of 105 species and 44 family of fishes. Total weight of sample was 55.3 kg, with the average stock abundance 0.27 kg/hour. Fishes catch composition were Apogonidae family 11,4%, Mulliidae family 35.7%, Nemipteridae family 16.3%, and Lutjanidae family 7,7%.  Richness value index ranged of 1862 –3.121. Equitability index ranged of 0.329 – 0.576.  Similarity index for station 3 and 6 was at 33.89% level; for station 1, 4, and 5 was at 20.31 % level,  and for station 4 and 5 was at 45,30% level from the maximum value of 100%.